PEMBUATAN FLAVOR LIMBAH UDANG (Panaeus monodon) DENGAN KOMPOSISI BUMBU YANG BERBEDA - Lucia Dewi Indrayani Manurung; Mustakim Mustakim; Erpiani Siregar (Fakultas Perikanan dan Kelautan, Universitas Riau, 2014)
Utilization of prawn waste into optimal flavor has not donein the freezingshrimp industries in Tanjung Balai City. More than 100kg of shrimp waste fromPT SEF Tanjung Balai each time the production. Therefore, it is necessary touseaflavor of shrimp waste with different seasonings formulation to determine the bestflavor formulations. The method usedwasan experimental method to utilizeshrimp waste into flavor. The designusedwas acompletely randomized design(CRD) with three non-factorial treatments and three replications. The resultsshowed the best treatment wasA 1 of organoleptic parameters, different treatmentA 1 to A 2 and A 3 of the flavor and aroma, texture and appearance while notsignificantly different. Proximatetest results showed each treatment were notsignificantly different. Likewise with TPC and PDA test molds and bacteria stillfound no safe limit.Keywords: Flavor, Shrimp Waste, Different Herb of Formulation